Asset prices and macroeconomic outcomes: A survey - Stijn Claessens; M. Ayhan Kose (Koç University-TÜSİAD Economic Research Forum (ERF), 2017)
This paper surveys the literature on the linkages between asset prices and macroeconomic outcomes. It focuses on three major questions. First, what are the basic theoretical linkages between asset prices and macroeconomic outcomes? Second, what is the empirical evidence supporting these linkages? And third, what are the main challenges to the theoretical and empirical findings? The survey addresses these questions in the context of four major asset price categories: equity prices, house prices, exchange rates and interest rates, with a particular focus on their international dimensions. It also puts into perspective the evolution of the literature on the determinants of asset prices and their linkages with macroeconomic outcomes, and discusses possible future research directions.
Keywords: D53; E21; E32; E44; E51; F36; F44; F65; G01; G10; G12; G14; G15; G21; 330; Equity prices; exchange rates; house prices; interest rates; credit; output; consumption; investment; real-financial linkages; macro-financial linkages; imperfections; frictions